Broken rotor bar fault diagnostic for DTC Fed induction motor using stator instantaneous complex apparent power envelope signature analysis - Lachtar Salah; Ghoggal Adel; Koussa Khaled; Bouraiou Ahmed; Attoui Issam (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
The broken rotor bar is an unexpected fault and a common cause of induction motor failures that threaten the structural integrity of electric machines. In this paper, a new approach to a broken rotor bar diagnosis, without slip estimation, based on the envelope of the stator instantaneous complex apparent power (SICAP) is proposed. The envelope is obtained from the SICAP modulation and then transferred to a computer for monitoring the characteristic frequency and its amplitude using the Fast Fourier Transform (FFT). For this purpose, the winding function approach (WFA) is used to simulate the broken rotor bar occurrence in a squirrel cage induction motor (SCIM) fed on direct torque control (DTC). The obtained simulation results confirm the interest and efficiency of the proposed technique. Even when the induction motor is operating at the no-load level condition, the proposed method is also efficient to detect the broken rotor bar fault at low slip.